Menelaah Realitas Perceraian Dalam Keluarga Katolik Dan Upaya Pencegahannya Melalui Penerangan Kanon 1141 - Pilipus Benizi Jindung; Karifansius Firman (JURNAL PASTORAL KATEKETIK, 2025)
This research aims to examine the reality of divorce in Catholic families and explore efforts to prevent it with reference to Canon 1141. Using a qualitative approach and a literature study method with the sources of books, journals, and the internet, this research reveals various factors that cause divorce in the context of Catholic families. The findings confirm that divorce is not a causeless event, but rather has complex root causes and consequences. Therefore, this research analyzes Canon 1141 as a framework for understanding and potential solutions. The canon, with its emphasis on certain aspects of marriage, is expected to provide light and guidance for Catholic families to face the challenges of maintaining the marriage bond. The findings of this study provide important input for Catholic families to better understand the nature of the sacrament of marriage as a holy bond that is eternal and indissoluble. In addition, the study also recommends increasing the Church's rigor in examining the preparation of couples who are getting married. A more comprehensive and in-depth preparation process is expected to help couples to understand the responsibilities and commitments they assume in a Catholic marriage. This is important to prevent desecration of the sacrament of marriage and minimize the potential for divorce. In conclusion, a deep understanding of the nature of Catholic marriage as a one and forever bond is key in preventing divorce among Catholic families.